THE USE OF MISTAKE BUSTER TECHNIQUE ON STUDENTS’ INTEREST IN LEARNING ENGLISH STRUCTURE AT ENGLISH STUDENTS OF DAYANU IKHSANUDDIN UNIVERSITY - Adu, Baharudin; Ilmi, Maulidayana (English Education Journal, 2024)
Problem statement of this research was whether there was a significant effect of the use Mistake Buster Technique on students’ interest in learning English structure in second semester at English students of Dayanu Ikhsanuddin University. Objective of the research was to find out the effect of Mistake Buster Technique on students' interest in learning English structure in second semester at English students of Dayanu Ikhsanuddin University. The research used a quantitative approach with the pre-experimental method. The population was the second semester at English students of Dayanu Ikhsanuddin University consist of 30 students. The sample was 30 students and was taken used the total sampling technique. The research found the mean score of pre-questionnaire was 73.53 and mean score of post-questionnaire was 82.20. And also the result p-value (sig.(2-tailed)) was 0.001 < 0.05, and t-test was 10.44. It was concluded that there was a significant effect of the use Mistake Buster Technique on students’ interest in Learning English structure at English students of Dayanu Ikhsanuddin University.